STUDI PENGETAHUAN DAN SIKAP TERHADAP PENGGUNAAN TUMBUHAN OBAT UNTUK MENGOBATI REMATIK PADA MASYARAKAT KOTA BAUBAU SULAWESI TENGGARA - Nur Wahyuni Arifin; Rahmawati Rahmawati; Sukmawati Sukmawati (As-Syifaa Jurnal Farmasi, 2022)
The use of plants as medicine or traditional ingredients has been carried out since ancient times by people in Indonesia, either as an effort to cure or prevent a disease. One of the diseases that is often found in the community is rheumatism. Rheumatism is a chronic systemic inflammatory disease that attacks the joints, especially the synovial joints. This study aims to identify and obtain an overview of knowledge and attitudes towards the use of medicinal plants to treat rheumatism in people in the city of Baubau, Southeast Sulawesi. This research uses descriptive non- experimental method. In this study, a questionnaire was used as an instrument to collect data. The number of samples in this study were 90 respondents with a sampling technique, namely proposive sampling. Based on the research that has been done, it is found that 65.6% have good knowledge and 57.8% of the respondents show a positive attitude. Thus it can be concluded that the people in Baubau City, Southeast Sulawesi have good knowledge and show a positive attitude towards the use of medicinal plants to treat rheumatism.